Eksplorasi Penalaran Matematis Siswa SD Kelas Tinggi dalam Menyelesaikan Masalah Numerasi: Tinjauan Epistemologis - Pangestika, Rintis Rizkia; Triyono, Ageng; Ngazizah, Nur; Sari, Septia Nurnita (Borobudur Educational Review, 2025)
Numeracy skills are a crucial foundation for developing logical and critical thinking among elementary school students. However, some students still struggle to connect mathematical concepts with real-life contexts. This study aims to analyze the mathematical reasoning patterns of elementary school students through an epistemological lens, focusing on how knowledge is acquired, structured, and utilized in solving contextual numeracy problems. This research employed a descriptive qualitative approach with a case study design. The participants consisted of six fifth-grade elementary students selected based on variations in their numeracy abilities. Data were collected through contextual numeracy tasks, observations of students’ thinking processes, and clinical interviews, then analyzed using an interactive model that involved data reduction, presentation, and verification. The findings indicate that students with high numeracy ability demonstrated conceptual and reflective reasoning patterns with well-organized knowledge structures, while students with moderate and low numeracy ability tended to exhibit procedural and fragmented thinking. Most students were unable to reflect on the validity of their knowledge, indicating a low level of epistemic awareness. These findings highlight the importance of numeracy learning that focuses not only on outcomes but also on students’ thinking processes and knowledge structures.